O-43 Surgeons report a high prevalence of musculoskeletal pain and home, work conflict. (14th March 2023) - Walker-Bone, Karen; Wood, Dan; D'Angelo, Stefania; Whitmore, Michael; Slight, Robert
Abstract : Introduction: Many surgeons in public health systems were deployed away from elective surgery during the COVID-19 pandemic and are now working under high pressure to reduce long waiting-lists including for people with malignancy. Methods: Using validated methodology, a questionnaire was circulated to surgeons via societies and social media. Anonymized data from voluntary respondents were collected via a centralized database. Results: 242 Surgeons responded amongst whom 170 (70.3%) were male. 14% were aged 25 to 34, 28% 35 to 44 years, 35% 45 to 54 years, 17% 55 to 64 and 5.8 % were aged 65 and over. 65.7% were urologists, 13.6% orthopaedics and trauma – others came from a range of surgical specialties. 46.3% suffered lower back pain in the prior month, 47.3% stated that this adversely affected work and recreational activities, 57.1% stated this had occurred > 5x in the previous year. Hip, neck and shoulder pain ranged from 6.2–43.8 % with up to 33.9% stating MSK symptoms had interfered with their work and (with the exception of shoulder pain (48.5%)) in each case >50% described symptoms > 5x pa. Only 8.7% reported receiving any ergonomic support to ensure comfort at work and 26.5% had ever received training in ergonomics. Surgeons reported 26% of the time they were often or always at work when required at home, with 48.8% reporting regular impact on private life. Many surgeons (84.4%) also report conflicting demands at work. Conclusions: Post-pandemic, surgeons report a high prevalence of musculoskeletal pain and work/life conflict. Surgeons could themselves take measures to mitigate these effects but planning and development of rotas and operating theatres could also be optimized. Maintaining the health of surgical staff is fundamental to patient safety and to retain highly-trained professionals within their discipline.